Preparation of graphene oxide/ waterborne polyurethane via boric acid cross-linked dopamine enhanced barrier and mechanical properties - Tian, Xinxin; Sun, Yinglu; Xie, Haopu; Shi, Biru; Zhong, Jiahui; Sheng, Dekun; Yang, Yuming (Frontiers in Materials, 2022)
Herein, a simple and efficient strategy was proposed to improve the gas barrier properties of waterborne polyurethane. Graphene oxide was first modified with dopamine and then cross-linked by boric acid to bring the graphene sheets closer together, thereby increasing the complexity of the gas pathway. FTIR, XPS, and SEM analyses proved that boric acid was uniformly dispersed into WPU, meanwhile, SEM images demonstrated the defects between the composites that were filled by the boric acid network. In addition, the mechanical properties of the composite were also enhanced. The tensile strength of the material increased from 25.2MPa to 34.2MPa, and Young’s modulus increased from 63.3MPa to 93.7MPa. The helium gas transmission rate of the composites was reduced by 85%, compared with the unmodified waterborne polyurethane film. The arrangement structure of DGO in polyurethane is the main reason for the excellent gas barrier performance of the material This work provides great potential with GO/ polyurethane for industrial application.